MORPHOMETRIC AND TESTICULAR CHARACTERISTICS OF BUFFALOS AT DIFFERENT AGES - Renata de Oliveira Santos Ramalho; Douglas Mena do Couto; Victor Cruz Rodrigues; André Mantegazza Camargo (Ciência Animal Brasileira, 2017)
We evaluated the live weight (LW), morphological and testicular measures and their correlations in 31 Mediterranean buffaloes at three ages. We used seven animals at 8 months of age (T1), 13 animals at the age of 10 months (T2), and 11 animals at the age of 12 months (T3) coming from a farm of the Coastal Lowlands of Rio de Janeiro. The following morphometric measurements and testes were evaluated: rump height (RH), withers height (WH), rump length (RL), round thickness (RT), scrotal circumference (SC), testicular length (TL), testicular width (TW). Testicular volume (TV) and body mass index (BMI) were also calculated. The testicular form was determined by the ratio between the TW and TL. We found the following means for the variables LW (240.57 ± 18.36; 259.38 ± 28.66; and 331.82 ± 63.23), WH (113.28 ± 2.44; 116.23 ± 4.74; and 121.45 ± 6.95cm), RH (116.07 ± 3.09; 117.54 ± 4.97; and 125.45 ± 6.92 cm), RL (34.86 ± 2.03; 36.35 ± 2.80; and 38.09 ± 3.24 cm), RT (39.07 ± 2.22; 40 ± 2.37; and 42.91 ± 3.97cm), BMI (187.37 ± 11.45; 191.69 ± 14.61; and 222.39 ± 23.57) regarding the treatments T1, T2, and T3, respectively. We found the following means for the variables SC (17.43±1.81; 19.08±1.98; and 22.11±3.25 cm), TL (8.28 ± 0.99; 9.27 ± 1.33; and 10.68 ± 1.47 cm), TW (3.25 ± 0.25; 3.90 ± 0.58; and 4.66 ± 0.80cm), and TV (109.43 ± 24.93; 198.36 ± 87.08; and 343.83 ± 183.04 cm3) regarding the treatments T1, T2, and T3, respectively. The predominant form in all treatments was long. There was no difference between the T1 and T2 for the studied variables. T3 had higher averages for LW, BMI, RH, SC, TV, and TW. For the variables WH, RL, TL, and RT there was no difference between T2 and T3. There was a correlation between measurements and testicular measures WH, RH, and RL and between SC and TV, TL, and TW. Keywords: body measures; buffaloes; testicular measures.